Mechanical and optical properties of CaCO3 lumen-loaded paper: effect of polyethylenimine and alum - Rohaya Othman,; Sarani Zakaria,; Chin-Hua Chia,; Ainun Zuriyati,; Nasharuddin Isa, (Universiti Kebangsaan Malaysia, 2010)
Precipitated calcium carbonate fillers were loaded into the lumen of bleached mixed tropical hardwood pulp using polyethylenimine (PEI) and alum. Our results indicated that the addition of (PEI) increased the degree of loading of precipitated calcium carbonate (PCC) into the lumen of fibers. The degree of loading also increased with the addition of alum together with PEI. The mechanical strengths of the produced lumen loaded paper increased with the addition of PEI and alum. Meanwhile the mechanical strength without alum had slightly increased the mechanical strengths of the paper. Electron micrographs revealed that the PCC fillers were successfully loaded into the lumen of the fibers.